1995
DOI: 10.1055/s-0038-1649835
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Disseminated Intravascular Coagulation in Relation to the Score when Treatment was Begun

Abstract: SummaryWe examined 395 patients with disseminated intravascular coagulation (DIC) divided into two groups: non-leukemic and leukemic. In 58% of the patients as a whole, treatment of DIC resulted in complete or partial remission, while exacerbation and death occurred in 31%. The efficacy of DIC treatment in the non-leukemic group was less than that in the leukemic group, indicating that the outcome of DIC depended, in part, on the underlying disease. We examined hemostatic indicators in relation to DIC score: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
2
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 162 publications
(151 citation statements)
references
References 23 publications
5
143
2
1
Order By: Relevance
“…The mortality of the late onset DIC was similar to that of pre-DIC. A previous report [8] also showed that outcome was improved by early DIC treatment. At present, no diagnostic criteria have yet been established for pre-DIC, and we therefore recommend that the treatment of DIC in non-overt-DIC positive should be started as early as possible in patients who are DIC absent but are positive for our modified non-overt DIC criteria.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The mortality of the late onset DIC was similar to that of pre-DIC. A previous report [8] also showed that outcome was improved by early DIC treatment. At present, no diagnostic criteria have yet been established for pre-DIC, and we therefore recommend that the treatment of DIC in non-overt-DIC positive should be started as early as possible in patients who are DIC absent but are positive for our modified non-overt DIC criteria.…”
Section: Discussionmentioning
confidence: 77%
“…The treatment efficacy in relation to the JMHW DIC score at the beginning of treatment showed that a greater efficacy was achieved in pre-DIC patients than in DIC patients [8]. The patient prognosis was progressively worse with increasing DIC score, suggesting that early diagnosis and early treatment are essential for improving the patient outcome.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The cutoff values of fibrin-related markers should be determined in overt-DIC criteria of ISTH. Early diagnosis and treatment of DIC were reported to be important to improve outcomes in DIC [24]. Among hemostatic molecular markers, plasma levels of D-dimer, TAT, PPIC, SF, tPA-PAI-I complex, and TM were significantly increased and plasma AT levels were significantly decreased in patients with DIC diagnosed by both ISTH and JMHW criteria.…”
Section: Discussionmentioning
confidence: 99%
“…This study comprised 1,789 patients admitted to the ICU of the Mie University School of Medicine from January 1998 through December 2001. Underlying conditions included post-operative patients (n ¼ 1,055), trauma (n ¼ 241), sepsis (n ¼ 73), heart disease (380), respiratory disease (299), aortic disease (183), cerebral disease (115), hepatic disease (24), and other diseases (547). Of the 1,789 patients, 127 (7.1%) died.…”
Section: Methodsmentioning
confidence: 99%